2010
DOI: 10.1103/physrevlett.104.241803
|View full text |Cite
|
Sign up to set email alerts
|

Observation of aJPC=1+Exotic Resonance in Diffractive Dissociation of190   GeV/c

Abstract: The COMPASS experiment at the CERN SPS has studied the diffractive dissociation of negative pions into the π- π- π+ final state using a 190  GeV/c pion beam hitting a lead target. A partial wave analysis has been performed on a sample of 420,000 events taken at values of the squared 4-momentum transfer t' between 0.1 and 1  GeV2/c2. The well-known resonances a1(1260), a2(1320), and π2(1670) are clearly observed. In addition, the data show a significant natural-parity exchange production of a resonance with spi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
70
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(79 citation statements)
references
References 24 publications
7
70
2
Order By: Relevance
“…Fitted P -wave resonance masses in both channels are found to be shifted upwards by typically 200 MeV/c 2 when introducing constant-phase model backgrounds as in Ref. [23]. In the present Letter, we refrain from proposing resonance parameters for the exotic P -wave or even the exotic F and H -waves observed here.…”
mentioning
confidence: 76%
See 3 more Smart Citations
“…Fitted P -wave resonance masses in both channels are found to be shifted upwards by typically 200 MeV/c 2 when introducing constant-phase model backgrounds as in Ref. [23]. In the present Letter, we refrain from proposing resonance parameters for the exotic P -wave or even the exotic F and H -waves observed here.…”
mentioning
confidence: 76%
“…For η π − , ambiguities occur when the PWA is extended beyond the dominant L = 1, 2 and 4 waves. We resolve this by requiring continuous behaviour of the dominant partial waves and of the Barrelet zeros [24]. The acceptable solutions agree within the statistical uncertainties with the solution selected here, which is the one with the smallest L = 3 contribution.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…Furthermore they concluded that this particle could be the first radial excitation of the l ¼ 1 state of a cq " c " q state while they identified another particle, the Yð4350Þ as the ground state. Recently the COMPASS collaboration [12] reported the observation of 1 ð1600Þ, a resonance with spin-exotic quantum numbers J PC ¼ 1 Àþ that can only be explained by assuming a hybrid or tetraquark constitution.…”
Section: Introductionmentioning
confidence: 99%